A practical guide to optical microscopy - Girkin, John (New York CRC Press, 2020)
"This practical guide to optical microscopy provides an outline of the physical principles behind different forms of optical microscopy, without using any complex maths. Detailed physics is provided in boxed sections, which can be overlooked by the non-specialist. This book is an invaluable tool for use within research groups and laboratories in physics and life sciences, acting as a first source of practical information to guide less experienced users (or those new to a particular methodology) on the specific methods available, enabling them to select the "right tool for the job". Features: Written to be understood by a non-optical expert but with inserts in the text which provide the physical science background if desired Brings together both conventional widefield and confocal microscopy with advanced non-linear and super resolution methods in one book The first book to cover all current optical microscopy methods at a sufficient depth so the user can understand how the method works"--
Keywords: Microscopy